Preclinical Studies of NEAST (Neutralizing Equine Anti-Shiga Toxin): A Potential Treatment for Prevention of Stec-Hus - Hiriart, Yanina (2019)
STEC-HUS is a clinical syndrome characterized by the triad of thrombotic microangiopathy, thrombocytopenia and acute kidney injury. Despite the magnitude of the social and economic problems caused by STEC infections, there are currently no specific therapeutic options on the market. HUS is a toxemic disorder and the therapeutic effect of the early intervention with anti-toxin neutralizing antibodies has been supported in several animal models. We have designed novel protein nanoparticles with very strong immunogenic capacity by inserting Stx1B and Stx2B subunits of Shiga toxin to Brucella abortus Lumazine Synthase (BLS). The chimeric BLS-StxBs particles elicited strong neutralizing antibodies against Shiga toxins in horses. Based on these responses, we produced NEAST (Neutralizing Equine Anti-Shiga Toxin), composed of purified F(ab’)2 fragments. In this report we present the preclinical analysis of this new treatment. As a general conclusion, NEAST shows a very strong neutralizing capacity against 8 Shiga toxin variants in preclinical models of STEC-HUS. NEAST is also able to neutralize pathologic effects after previous exposure to Shiga Toxin, defining a potential therapeutic window. Besides, NEAST shows an excellent pharmacokinetics and safety profile in animal models. Overall, these results indicate that NEAST is a very good drug candidate for preventing the onset of HUS in STEC-infected patients and validate the conduction of a first in human clinical study at the Hospital Italiano de Buenos Aires in order to evaluate its safety and pharmacokinetic profiles in healthy adult volunteers.